PROFITABILITAS, STRUKTUR MODAL DAN NPL DALAM MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN MODERASI VARIABEL UKURAN PERUSAHAAN - Alip, Gilang Permata Nur; Arief, Muhammad Yahya; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
Banking companies are a pillar of a nation’s economy. That is, it plays a vital cog in the Indonesian economy. They must be able to facilitate and ease creditors, debtors and investors to invest and distribute capital to those in need. The aim of this research is to examine the influence of profitability, capital structure and Non-Performing Loans (NPL) on company values which are moderated by company size. This research is explanatory research. The population of this research is banking companies listed on the Indonesian Stock Exchange for 2019-2022. The sampling technique is purposive sampling. Data analysis and hypothesis testing use Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application showed that profitability did not have a significant effect on company value, capital structure had a significant effect on company value, Non-Performing Loans (NPL) did not have a significant effect on company value. The results of indirect effect hypothesis test showed that the profitability variable had no significant effect on company value moderated by company size, capital structure did not have a significant effect on company value moderated by company size.